KONSEPTUALISASI PENCIPTAAN KINERJA PEMASARAN OBAT: SEBUAH PENGEMBANGAN MODEL TEORITIK - Bagus Putu Yudhia Kurniawan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2016)
Indonesia is a very attractive market in the marketing of herbal medicine. Until now recorded 61% of the 255 million population of Indonesia had consumed herbal medicine known as “jamu”. The phenomenon of the increase in market demand - coupled climate of intense competition with the opening of the free market provides opportunities and challenges for pharmaceutical companies based herbal medicine (herbal medicine company) to move a step forward in increasing the innovation and the role of information systems to increase marketing performance. The purpose of this study was to analyze and examine the influence of innovation and information systems on performance marketing, the influence of information systems on innovation, and the influence of information systems on the performance marketing of the herbal medicine company through innovation. This study was a survey research type used for explanatory or confirmatory purposes. This study was use complete enumeration method or census, so sampling technique is also not needed. The analysis technique used is path analysis. The results showed that the innovation and information systems directly affect, positively and significantly to the marketing performance. The information system directly affect, positively and significantly to innovation, and through innovation, information systems was also positive and significant effect on the marketing performance of the herbal medicine company